ANALISIS PENGARUH SUHU RUANGAN TERHADAP KONSENTRASI BEKERJA KARYAWAN PADA PT TEAM METAL INDONESIA - Pratama, Ferdian; Sri Zetli (Computer Science and Industrial Engineering, 2024)
The temperature in the room in the milling section reaches 37'C which is not in accordance with the limit of room temperature regulations. Employees who are too tired to work with hot room conditions make work concentration unfocused and can endanger the workers themselves. The purpose of this study is to determine the state of room temperature at PT Team Metal Indonesia, determine the concentration of working employees at PT Team Metal Indonesia and the relationship between room temperature and concentration of working employees at PT Team Metal Indonesia. This study uses a simple regression method. Based on the results of the study, it is known from the measurement of room temperature that the average value is 39.77 and the percentage value is 79.54%. This value is not good at the room temperature in the company. It is known from the measurement results on work concentration that the average value is 40 and the percentage value is 80%. This value is not good for the concentration of work felt at the company and there is a significant influence between room temperature and work concentration on milling department employees at PT Team Metal Indonesia.